Orbitofrontal control of visual cortex gain promotes visual associative learning - Dechen Liu (Nature Portfolio, 2020)
The orbitofrontal cortex (OFC) encodes expected outcomes and plays a key role in outcome-guided behavior. The authors show here that the top-down projection from the OFC to the visual cortex drives visual associative learning by modulating the response gain of V1 neurons to non-relevant stimuli.